Outcomes after simultaneous pancreas–kidney transplantation from donation after circulatory death donors: A UK registry analysis. Issue 11 (28th June 2021) - Callaghan, Chris J.; Ibrahim, Maria; Counter, Claire; Casey, John; Friend, Peter J.; Watson, Christopher J. E.; Karydis, Nikolaos
Abstract : There are concerns that simultaneous pancreas–kidney (SPK) transplants from donation after circulatory death (DCD) donors have a higher risk of graft failure than those from donation after brain death (DBD) donors. A UK registry analysis of SPK transplants between 2005 and 2018 was performed. Pancreas survivals of those receiving organs from DCD or DBD donors were compared. Multivariable analyses were used to adjust for baseline differences between the two groups and to identify factors associated with pancreas graft loss. A total of 2228 SPK transplants were implanted; 403 (18.1%) were from DCD donors. DCD donors were generally younger, slimmer, less likely to have stroke as a cause of death, with lower terminal creatinines and shorter pancreas cold ischemic times than DBD donors. Median (IQR) follow‐up was 4.2 (1.6–8.1) years. On univariable analysis, there were no statistically significant differences in 5‐year death‐censored pancreas graft survival between the two donor types (79.5% versus 80.4%; p  = .86). Multivariable analysis showed no statistically significant differences in 5‐year pancreas graft loss between transplants from DCD ( n  = 343) and DBD ( n  = 1492) donors (hazard ratio 1.26, 95% CI 0.76–1.23; p  = .12). The findings from this study support the increased use of SPK transplants from DCD donors. Abstract : This UK national registry analysis finds no statistically significant differences, even after risk adjustment, in pancreas graft survival between simultaneous pancreas–kidney transplants from controlled donation after circulatory death donors with those from donation after brain death donors.